(untitled) (Altre Modernità, 2024)
In 1798, the introduction of smallpox vaccination produced a complex web of tensions that sparked a fierce debate fuelled by both medical treatises and literary texts. Through cowpox inoculation, Edward Jenner proposed not only to tame a monstrous disease but also to introduce an agent of moral and social reform. At the same time, the rural background of his discovery prompted new reflection on the unstable boundaries separating medical science from the popular culture of the lower classes, particularly as it relates to women’s lore. The progressively broader acceptance achieved by the cowpox vaccine shows that literature can have a powerful impact on the medico-cultural domain. By generating and disseminating a rhetoric which controlled excess, smoothed irregularity, and subdued disorder, writers such as Bloomfield, Anstey, Williams, Coleridge, and Southey helped normalize a potentially subversive discourse, transforming it into a cornerstone that reinforced pre-existing patterns of inequality.